Calibrating SANS data for instrument geometry and pixel sensitivity effects: access to an extended Q range. Issue 5 (14th September 2017) - Karge, Lukas; Gilles, Ralph; Busch, Sebastian
Abstract : A calibration procedure for small‐angle neutron scattering (SANS) data is presented, where geometric effects are treated analytically and voxel sensitivities are calibrated with measurements of an arbitrary scatterer. This allows correction of the measured intensities with a single measurement, without the need to measure an isotropic scatterer at all used instrumental settings. Abstract : An improved data‐reduction procedure is proposed and demonstrated for small‐angle neutron scattering (SANS) measurements. Its main feature is the correction of geometry‐ and wavelength‐dependent intensity variations on the detector in a separate step from the different pixel sensitivities: the geometric and wavelength effects can be corrected analytically, while pixel sensitivities have to be calibrated to a reference measurement. The geometric effects are treated for position‐sensitive 3 He proportional counter tubes, where they are anisotropic owing to the cylindrical geometry of the gas tubes. For the calibration of pixel sensitivities, a procedure is developed that is valid for isotropic and anisotropic signals. The proposed procedure can save a significant amount of beamtime which has hitherto been used for calibration measurements.